Students’ Satisfaction on Academic Services in Higher Education Using Importance-Performance Analysis - Suroto, Suroto; Nindiani, Aina; Purba, Humiras Hardi (ComTech: Computer, Mathematics and Engineering Applications, 2017)
The objective of this research was to determine the students’ satisfaction level on the academic services provided by the accounting program at a private university in Jakarta and to evaluate attributes that should be improved. The data were obtained from questionnaires by using 5 quality dimensions. There are tangible, reliability, responsiveness, assurance, and empathy. Moreover, the data were processed by using Excel, SPSS 20, Customer Satisfaction Index (CSI) to determine the level of customer satisfaction, and also Importance-Performance Analysis (IPA) to determine the attributes of service be repaired and maintained. The results show that the CSI is 71%, which means that the majority of customers are satisfied with the performance of the service quality of accounting program. Meanwhile, the results of IPA indicate that the improvement priorities have two attributes in quadrant 1. They are the availability of space to support student activities and the availability of books and teaching materials related to the syllabus. These attributes are the top priority because the importance level is high while the performance level is low from the customers’ point of view.